A method for preparing silicon-based negative electrode material

By using carbon nanotube modified silicon-based materials of different sizes and dispersion methods in lithium-ion batteries, a high-strength conductive network is formed, which solves the problems of poor conductivity and poor cycle stability of silicon-based negative electrode materials, and achieves a significant improvement in rate performance and structural stability.

CN115132982BActive Publication Date: 2025-04-01WANHUA CHEM (SICHUAN) CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210616558.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-01
Publication Date
2025-04-01
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

The silicon-based negative electrode material in existing lithium-ion batteries has poor conductivity and uneven carbon coating, resulting in poor cycle stability and rate performance.

Method used

By adding carbon nanotubes of different sizes and dispersion methods to the silicon-based material modification, silicon-based modified material and graphite composite and composite material post-treatment process, a high-strength conductive network is formed to improve the conductivity and structural stability of the material.

Benefits of technology

It significantly improves the conductivity and cyclic stability of the silicon-based negative electrode material, enhances the rate performance and mechanical strength of the material, and effectively alleviates the problem of volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003673485060000201
    Figure BDA0003673485060000201
  • Figure HDA0003673485070000011
    Figure HDA0003673485070000011
  • Figure HDA0003673485070000021
    Figure HDA0003673485070000021
Patent Text Reader

Abstract

The present invention discloses a method for preparing a silicon-based negative electrode material. By adding carbon nanotubes of different sizes and dispersion modes in three stages of silicon-based material modification, silicon-based modified material and graphite composite, and silicon-based modified composite material post-processing, the dispersion uniformity of silicon-based material and carbon nanotubes in the entire composite material is significantly improved, thereby greatly improving the utilization rate of active substances and carbon nanotubes. Carbon nanotubes of different diameters and lengths cross each other and form a high-strength conductive network, which can not only serve as a supporting matrix of the entire silicon-based composite material to buffer volume expansion during the cycle, but also build a conductive channel between the silicon-based material and the surrounding conductive material to avoid loose contact in the conductive network, thereby solving the problem of poor conductivity of the composite material and contact between the silicon-based material and the electrolyte. The silicon-based negative electrode material is applied to the negative electrode of a lithium-ion battery to effectively improve the battery's cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery materials, and in particular to a method for preparing a silicon-based negative electrode material for a lithium-ion battery. Background Art

[0002] Silicon has a high theoretical specific capacity (theoretical specific capacity 4200mAh / g) and a low discharge potential, making it an ideal negative electrode material for lithium batteries. However, during the cyclic charge and discharge process, the volume of silicon expands significantly, loosening the contact between the active material and the current collector, resulting in poor cycle stability. In addition, silicon-based materials also have the problem of poor conductivity. In order to improve the conductivity of silicon-based negative electrode materials, the most commonly used method is CVD carbon coating. However, there are problems such as uneven coverage of the carbon layer and loose contact. The expansion of silicon will cause the carbon layer to rupture, resulting in deterioration of its cycle performance.

[0003] In order to overcome this problem, researchers have conducted a lot of research work in recent years. By reducing the size of silicon materials, reducing the stress generated during volume expansion, improving the structural stability of silicon, and shortening the transmission distance of lithium ions, the electrochemical performance of silicon negative electrodes can be improved. On this basis, the introduction of a conductive buffer matrix can improve the conductivity of silicon materials while using the elasticity, stability and other properties of the matrix to effectively control and alleviate the volume change of silicon materials and maintain the integrity of the overall structure of the material. As a new type of conductive material, carbon nanotubes have a unique structure and unique properties (such as high conductivity and tensile strength). They have a high aspect ratio and excellent conductivity, and can effectively form a three-dimensional conductive network. A low addition amount can improve the energy density of lithium-ion batteries and extend the cycle life of batteries. Therefore, the method of incorporating CNTs as an additive into active negative electrode materials is an effective strategy to form a conductive network in the electrode. However, the initial powder of carbon nanotubes is mostly entangled in the form of agglomerates or bundles in microscopic morphology, and has a large specific surface area, which makes the initial powder of carbon nanotubes difficult to disperse.

[0004] Patent CN106169564B discloses a silicon-carbon nanotube sphere and a preparation method thereof, wherein the silicon dispersion is obtained by ultrasonically dispersing nano-silicon particles into an aqueous solution and performing a hydrothermal reaction, and then carboxylated carbon nanotubes are added and ultrasonically mixed and then spray granulated to obtain the silicon-carbon nanotube sphere. Firstly, simple ultrasonic mixing cannot achieve uniform dispersion of carbon nanotubes with a large specific surface area. Secondly, no chemical bonds are formed between the nano-silicon particles and the carboxylated carbon nanotubes, and they are only connected by van der Waals forces. The bonding force between the two is poor, and they are prone to fall off, which ultimately leads to poor electrochemical performance of the material.

[0005] Patent CN109301215B discloses a high-capacity silicon-carbon negative electrode active material, a preparation method and an application thereof, wherein nano-silicon, flake graphite, carbon nanotubes and a carbon source are uniformly dispersed through a one-step ball milling process, wherein the mass fraction of carbon nanotubes is as high as 5% to 10%, and the length is relatively long at 20-100 μm. At a relatively low ball milling speed, the shear dispersion of the carbon nanotubes cannot be achieved, and it is difficult to achieve uniform dispersion of the carbon nanotubes in the entire material system and they are easy to agglomerate. A relatively high ball milling speed easily causes the added flake graphite to be unable to play the role of a nano-silicon carrier after ball milling. Therefore, this method seems simple and efficient but cannot achieve a high dispersion of carbon nanotubes. Moreover, the silicon-carbon material microspheres prepared by spray drying the slurry after ball milling have a relatively large particle size and are simply compounded with graphite, and cannot achieve close contact between the silicon-based material and the graphite, thereby affecting the electrochemical properties of the final material.

[0006] In summary, there is an urgent need to develop a silicon-based negative electrode material and a preparation method thereof, which can improve the doping efficiency and dispersion stability of carbon nanotubes, and can also improve the conductivity of silicon-based negative electrode materials. Therefore, the influence of the combination of carbon nanotubes, silicon-based materials and graphite on the material properties is studied, so as to find the best combination method, so that the performance of all aspects of the material can be maximized to meet the safety performance and quality requirements of lithium-ion batteries. Summary of the invention

[0007] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a silicon-based negative electrode material for a lithium-ion battery, which solves the above-mentioned defects in the prior art by adding carbon nanotubes of different sizes and dispersion modes in three stages: modification of silicon-based materials, composite of silicon-based materials and graphite, and post-processing of composite materials.

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A method for preparing a silicon-based negative electrode material comprises the following steps:

[0010] (1) Silicon-based material modification: the silicon-based material and CNT-Ⅰ dispersion slurry are mixed, separated, dried, and sintered under an inert atmosphere to obtain a silicon-based modified material;

[0011] (2) Composite of silicon-based modified material and graphite: The silicon-based modified material, graphite and CNT-II dispersed slurry are mixed and spray-dried to obtain a silicon-based modified composite material;

[0012] (3) Post-treatment of silicon-based modified composite materials: The CNT-III dispersed powder uniformly dispersed in the coating agent is used to fill and coat the silicon-based modified composite materials, and then carbonized at high temperature.

[0013] As a preferred scheme, the preparation method of the CNT-Ⅰ dispersed slurry of the present invention comprises the following steps: adding a silane coupling agent to an ethanol aqueous solution, mixing evenly, adding hydroxyl carbon nanotubes CNT-Ⅰ and an organic carbon source to disperse evenly, and then heating, stirring and refluxing to obtain a CNT-Ⅰ dispersed slurry.

[0014] As a preferred solution, the method for preparing the CNT-Ⅱ dispersed slurry of the present invention comprises the following steps: uniformly mixing a binder, a dispersant and a solvent a, adding single-walled carbon nanotubes CNT-Ⅱ and a solvent b thereto, and dispersing to obtain a CNT-Ⅱ dispersed slurry.

[0015] As a preferred scheme, the preparation method of CNT-Ⅲ dispersed powder uniformly dispersed in the coating agent described in the present invention comprises the following steps: multi-walled carbon nanotubes CNT-Ⅲ and coating agent powder are crushed in a gas flow mill to obtain multi-walled carbon nanotubes and coating agent mixed powder, and then kneaded in a kneader, the discharged material is cooled and crushed, and then put into a gas flow mill for crushing.

[0016] As a preferred solution, step (3) of the present invention comprises the following steps: filling and coating the silicon-based modified composite material with CNT-III dispersed powder uniformly dispersed in the coating agent by heat treatment in a heating mixing device under the protection of an inert atmosphere, and then performing high-temperature carbonization under an inert atmosphere.

[0017] Preferably, in the preparation method of the CNT-Ⅰ dispersed slurry, the silane coupling agent is an aminosilane coupling agent, and suitable examples include but are not limited to one or more of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane, preferably one or more of γ-aminopropylmethyldiethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane. Hydroxylated carbon nanotubes CNT-I are modified by aminosilane coupling agent. After hydrolysis, the silane coupling agent condenses with the hydroxyl groups on the surface of the hydroxylated carbon nanotubes CNT-I. The amino groups in the silane coupling agent can form hydrogen bonds with the surface hydroxyl groups of the silicon-based material. Through the action of the silane coupling agent, the hydroxylated carbon nanotubes CNT-I are better dispersed on the surface of the silicon-based material, increasing the binding force between the two, thereby enhancing the conductivity of the silicon-based material.

[0018] Preferably, in step (1), the silicon-based material is one or more of silicon, silicon monoxide and silicon alloy, more preferably nano-silicon, and the D50 of the silicon-based material is 100-300 nm.

[0019] Preferably, in the preparation method of the CNT-I dispersion slurry, the diameter of the hydroxy carbon nanotube is 5nm-15nm, the length is 0.5μm-2μm, and hydroxy multi-walled carbon nanotubes are preferred. Short straight multi-walled carbon nanotubes have better rigidity and can more easily penetrate the pyrolytic carbon layer and maintain good electrical contact with the surrounding conductive materials. Suitable examples include but are not limited to XFM05 from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.

[0020] Preferably, in the preparation method of the CNT-I dispersed slurry, the organic carbon source is one or more of citric acid, sucrose, glucose, polyvinyl pyrrolidone, polyvinyl alcohol, asphalt, phenolic resin, asphalt, preferably one or more of polyvinyl pyrrolidone, phenolic resin, asphalt.

[0021] Preferably, in the preparation method of the CNT-I dispersed slurry, based on the total mass of hydroxyl carbon nanotubes CNT-I, silane coupling agent, organic carbon source and ethanol aqueous solution as 100%, the mass of hydroxyl carbon nanotubes CNT-I accounts for 0.1-1.5%, the mass of silane coupling agent accounts for 0.02-0.3%, and the mass of organic carbon source accounts for 0.1-1%.

[0022] Preferably, in the method for preparing the CNT-I dispersion slurry, the mass ratio of the silane coupling agent to the water in the ethanol aqueous solution is 1:(4-8).

[0023] Preferably, in the method for preparing the CNT-I dispersed slurry, the dispersion is carried out by ultrasound, the ultrasound frequency is 20-40 kHz, and the ultrasound time is 0.5-1.5 h.

[0024] Preferably, in the method for preparing the CNT-I dispersion slurry, the heating temperature is 60-100° C. and the heating time is 2-6 h.

[0025] Preferably, in step (1), the mass ratio of silicon-based material to CNT-I is (10-30):(0.1-1.5), so that the hydroxy carbon nanotubes are fully dispersed in the silicon-based material.

[0026] Preferably, in step (1), the inert atmosphere is Ar or N2, the heating rate is 3°C-10°C / min, the sintering temperature is 600-800°C, and the holding time is 2-6h, so as to facilitate the thermal decomposition of the silane coupling agent and the organic carbon source.

[0027] In the preparation method of the present invention, the pyrolytic carbon formed after the pyrolysis of the added organic carbon source and the silane coupling agent enables the hydroxy carbon nanotubes to be embedded in the carbon coating layer and better fixed on the surface of the silicon-based material, thereby enhancing the cycle stability of the silicon-based material.

[0028] Preferably, in the method for preparing the CNT-Ⅱ dispersed slurry, the binder mainly includes one or more of sucrose, glucose, starch, phenolic resin, urea-formaldehyde resin, cellulose acetate, citric acid, and asphalt.

[0029] Preferably, in the preparation method of the CNT-Ⅱ dispersed slurry, the dispersant is a polymer dispersant, including one or more of polyvinyl pyrrolidone and its modified copolymers, polyacrylic acid and its modified copolymers, polyacrylate dispersants, polyvinyl alcohol dispersants and their modified resin polymers, polyethylene glycol, and polyoxyethylene dispersants. Suitable examples include but are not limited to Triton X-100.

[0030] Preferably, in the method for preparing the CNT-II dispersed slurry, the solvent a or the solvent b is one or more of N-methylpyrrolidone, ethanol, isopropanol and water, preferably ethanol.

[0031] Preferably, in the preparation method of the CNT-Ⅱ dispersed slurry, the diameter of the single-walled carbon nanotube CNT-Ⅱ is 1nm-3nm, the length is 15μm-40μm, and the aspect ratio is greater than 10000. The conductive carbon tube with a high aspect ratio has better flexibility and conductivity, which can keep the conductive connection network of the material as a whole and improve the rate performance. Suitable examples include but are not limited to NTP8022 of Shenzhen Nanoport Co., Ltd.

[0032] Preferably, in the preparation method of the CNT-Ⅱ dispersed slurry, based on the total mass of CNT-Ⅱ, binder, dispersant and solvent a as 100%, CNT-Ⅱ accounts for 0.1-1%, binder accounts for 3-10%, dispersant accounts for 0.05-0.5%, and solvent a accounts for 88.7-96.85%.

[0033] Preferably, in the method for preparing the CNT-Ⅱ dispersed slurry, the mass ratio of solvent b to solvent a is (1.17-1.66):1.

[0034] Preferably, in the method for preparing the CNT-Ⅱ dispersed slurry, the dispersion is carried out by ultrasound, the ultrasound frequency is 40-60 kHz, and the ultrasound time is 0.5-1.5 h.

[0035] Preferably, in step (2), the mass ratio of the graphite, CNT-II and the silicon-based material in step (1) is (50-80); (0.1-1): (10-30).

[0036] Preferably, in step (2), the graphite is one or more of natural graphite, artificial graphite, and mesophase carbon microspheres, preferably artificial graphite with a particle size of 6-10 μm.

[0037] Preferably, in step (2), the spray drying pressure is 0.3-0.5 MPa, the inlet temperature is 120-180°C, and the outlet temperature is 60-100°C.

[0038] Preferably, in step (2), the silicon-based modified material is embedded between graphite and graphite by spray drying and bonded together by a binder. The outer layer of graphite effectively limits the volume expansion and pulverization of the silicon-based material. CNT-Ⅱ has high flexibility and conductivity. By connecting with CNT-I, it promotes the overall electronic transmission of the material and keeps the silicon-based material in close contact with the graphite, thereby greatly improving the rate performance and cycle stability of the entire material.

[0039] Preferably, in the method for preparing the CNT-III dispersed powder uniformly dispersed in the coating agent, the multi-walled carbon nanotube CNT-III has a diameter of 20-40 nm and a length of 10-30 μm, which is less likely to agglomerate than single-walled carbon nanotubes with a high aspect ratio, and is conducive to uniform dispersion in the coating agent. Suitable examples include, but are not limited to, TNIM6 from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences.

[0040] Preferably, in the method for preparing the CNT-III dispersed powder uniformly dispersed in the coating agent, the coating agent includes one or more of a thermoplastic resin and asphalt, preferably asphalt, more preferably one or more of petroleum asphalt and coal-based asphalt; as a preferred embodiment, the softening point of the asphalt is 200-300°C, preferably 230-280°C, and the particle size D50 is 50-100μm.

[0041] Preferably, in the method for preparing the CNT-III dispersed powder uniformly dispersed in the coating agent, the mass ratio of the multi-walled carbon nanotubes CNT-III to the coating agent is (1-10):100.

[0042] Preferably, in the method for preparing the CNT-III dispersed powder uniformly dispersed in the coating agent, the kneading temperature is 245-300° C. and the time is 2-5 hours.

[0043] Preferably, in step (3), the mass ratio of CNT-II to CNT-III contained in the silicon-based modified composite material is (0.1-1): (0.01-1).

[0044] A preferred solution is a method for preparing CNT-III dispersed powder uniformly dispersed in a coating agent, comprising the following steps: airflow crushing of multi-walled carbon nanotubes CNT-III and coating agent powder, kneading, cooling and crushing of the discharged material, and airflow crushing to uniformly disperse the crushed multi-walled carbon nanotubes CNT-III in the coating agent. This method can achieve uniform dispersion of multi-walled carbon nanotubes CNT-III in the coating agent without adding a dispersant. Compared with mechanical stirring, ultrasonic dispersion and chemical dispersion preparation processes, it can better break up agglomerated carbon nanotubes, shorten carbon nanotubes, and maintain a good dispersion state of the two.

[0045] Preferably, in the step (3), the coating agent in the CNT-III dispersed powder is softened by low-temperature heat treatment, and the silicon-based modified composite material is filled and coated, thereby achieving the filling of the internal voids of the silicon-based modified composite material microspheres and the modification and coating of the surface. First, the CNT-III filled into the microspheres will establish a connection with the conductive network formed by CNT-I and CNT-II to form a more stable three-dimensional network structure. At the same time, the coating agent pyrolytic carbon makes the internal structure of the entire composite material dense and the surface uniform, which plays a role in buffering the expansion of the internal material, avoiding the contact of the silicon-based material with the electrolyte, and improving the stability of the material.

[0046] Preferably, in the step (3), the filling and coating are followed by low-temperature heat treatment in the presence of an inert gas, the inert gas is argon and / or nitrogen, the low-temperature heat treatment temperature is 300-400°C, and the time is 1-5h.

[0047] Preferably, in step (3), the high temperature carbonization has a heating rate of 3°C-10°C / min, a temperature of 800-1100°C, and a holding time of 0.5-5h.

[0048] The preparation method of the present invention significantly improves the dispersion uniformity of silicon-based materials and carbon nanotubes in the entire composite material by adding carbon nanotubes CNT-I, CNT-II and CNT-III of different sizes and dispersion modes in three stages of silicon-based material modification, silicon-based modified material and graphite composite and silicon-based modified composite material post-treatment, thereby greatly improving the utilization rate of active substances and carbon nanotubes. The formed carbon nanotube conductive network provides a more convenient channel for the migration of electrons, and can effectively alleviate the volume expansion of silicon-based negative electrode materials, which is conducive to forming a cross-linked network between the components to enhance the elasticity and strength of the silicon-based negative electrode material, thereby improving the rate performance and cycle performance of the silicon-based composite material.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) The present invention significantly improves the dispersion uniformity of silicon-based materials and carbon nanotubes in the entire composite material by adding carbon nanotubes of different sizes and dispersion modes in three stages: modification of silicon-based materials, composite of silicon-based modified materials and graphite, and post-processing of the composite material, thereby greatly improving the utilization rate of active substances and carbon nanotubes.

[0051] (2) The present invention uses carbon nanotubes of different diameters and lengths to cross each other and form a high-strength conductive network. The conductive network can serve as a buffer skeleton and build a fast electron transmission channel between the silicon-based material and the surrounding conductive material to avoid loose contact in the conductive network. Even if the volume of the silicon-based particles changes significantly, the conductive network can still keep the particles in close contact with the graphite, which is more conducive to solving the problem of poor conductivity of the composite material and the contact between the silicon-based material and the electrolyte, thereby effectively improving the cycle stability and rate performance of the battery.

[0052] (3) The present invention utilizes a silane coupling agent to modify carbon nanotubes, so that the silane coupling agent is hydrolyzed and then condensed with the hydroxyl groups on the surface of the carbon nanotubes. Then, a silicon-based material is added so that the hydroxyl groups on the surface of the silicon-based material form hydrogen bonds with the amino groups in the silane coupling agent. Through the action of the silane coupling agent, the carbon nanotubes are better dispersed on the surface of the silicon-based material, thereby improving the compatibility and bonding ability of the carbon nanotubes and the silicon-based material. After the silane coupling agent disperses and modifies the carbon nanotubes, it can also be pyrolyzed with an organic carbon source to form a carbon coating layer, and the doped N in the carbon coating layer will enhance its interaction with the active material during cycling, thereby improving its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0054] Figure 1 The SEM of porous microspheres of silicon-based modified composite material obtained after spray drying in Example 1;

[0055] Figure 2 This is the SEM of the porous microspheres filled and coated with silicon-based modified composite material obtained after spray drying in Example 1. DETAILED DESCRIPTION

[0056] The following examples are implemented on the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples. The methods used in the following examples are conventional methods unless otherwise specified.

[0057] Example 1

[0058] (1) preparing a CNT-I dispersion slurry: adding γ-aminopropyltriethoxysilane, a silane coupling agent, to a solution of ethanol and water and stirring the mixture evenly, wherein the mass ratio of γ-aminopropyltriethoxysilane to water is 1:6; adding hydroxy carbon nanotubes CNT-I with a diameter of 5-10 nm and a length of 2 μm and polyvinylpyrrolidone in a mass ratio of CNT-I, γ-aminopropyltriethoxysilane and polyvinylpyrrolidone of 1:0.2:0.5, wherein the solid content of CNT-I in the slurry is 1%, ultrasonically treating the mixture at a frequency of 30 kHz for 1 h, and then heating the mixture to 80°C and stirring and refluxing for 4 h to obtain a CNT-I dispersion slurry;

[0059] (2) Modification of silicon-based materials: Add nano-silicon with a particle size of 100 nm to the CNT-I dispersion slurry, wherein the mass ratio of nano-silicon to CNT-I is 20:1, stir and disperse at 600 r / min for 1.5 h, separate and dry, and heat to 600 °C at 3 °C / min in a N2 atmosphere for 4 h to obtain a silicon-based modified material;

[0060] (3) preparing CNT-II dispersion slurry: adding citric acid and Triton X-100 to ethanol a and stirring evenly, adding single-walled carbon nanotubes CNT-II with a diameter of 1-1.5 nm and a length of 30-40 μm, wherein the mass ratio of CNT-II, citric acid, Triton X-100 and ethanol a is 0.5:8.3:0.2:91, and then adding a certain amount of ethanol b, wherein the mass ratio of ethanol b to ethanol a is 1.48:1, stirring and dispersing at 800 r / min for 1.5 h, and then ultrasonically dispersing at a frequency of 50 kHz for 1 h to obtain CNT-II dispersion slurry;

[0061] (4) Composite of silicon-based modified material and graphite: The silicon-based modified material and artificial graphite with a particle size of 8 μm are added to the CNT-II dispersed slurry, wherein the mass ratio of nano-silicon, artificial graphite and CNT-II is 20:66:0.5, and then dispersed at a high speed of 1500 r / min for 2 h to obtain a dispersed slurry with a solid content of 30%, and granulated using a two-fluid spray equipment. The spray drying pressure is 0.4 MPa, and the inlet and outlet temperatures are set to 160° C. and 80° C., respectively, to obtain a silicon-based modified composite material;

[0062] (5) Preparation of CNT-III dispersed powder: Multi-walled carbon nanotubes CNT-III with a diameter of 20-30 nm and a length of 30 μm and coal tar pitch with a softening point of 270°C and a particle size of 50 μm are added into a jet mill, the mass ratio of multi-walled carbon nanotubes CNT-III to coal tar pitch being 10:100, and the mixture is crushed at a frequency of 150 Hz to obtain mixed particles of multi-walled carbon nanotubes and asphalt, and then heated to 285°C in a kneader and kneaded for 3 h. The discharged material is cooled and crushed, and then put into a jet mill and crushed again to obtain CNT-III dispersed powder uniformly dispersed in the asphalt;

[0063] (6) Post-treatment of silicon-based modified composite materials: The silicon-based modified composite materials and CNT-III dispersed powders are added into a high-temperature coating kettle, wherein the mass ratio of CNT-II to CNT-III in the silicon-based modified composite materials is 5:3, and stirred at a speed of 300 r / min under the protection of N2 atmosphere, and heated to 360°C for heat treatment for 2 h to fully soften the CNT-III dispersed powder to fill and coat the silicon-based modified composite materials, and then heated to 1100°C at 3°C / min under the protection of N2 in a high-temperature box furnace and kept for 2 h to obtain silicon-based negative electrode materials for lithium-ion batteries.

[0064] Example 2

[0065] (1) preparing a CNT-I dispersion slurry: adding γ-aminopropyltriethoxysilane, a silane coupling agent, to a solution of ethanol and water and stirring evenly, wherein the mass ratio of γ-aminopropyltriethoxysilane to water is 1:6; adding hydroxy carbon nanotubes CNT-I with a diameter of 10-15 nm and a length of 3 μm and polyvinylpyrrolidone according to a mass ratio of CNT-I, γ-aminopropyltriethoxysilane and polyvinylpyrrolidone of 1.5:0.3:1, wherein the solid content of CNT-I in the slurry is 1.5%, ultrasonicating at a frequency of 40 kHz for 0.5 h, and then heating to 80° C. and stirring under reflux for 4 h to obtain a CNT-I dispersion slurry;

[0066] (2) Modification of silicon-based materials: Add nano-silicon with a particle size of 100 nm to the CNT-I dispersion slurry, wherein the mass ratio of nano-silicon to CNT-I is 30:1.5, stir and disperse at 800 r / min for 1 h, separate and dry, and heat to 600°C in a N2 atmosphere at 10°C / min for 6 h to obtain a silicon-based modified material;

[0067] (3) preparing CNT-II dispersion slurry: adding sucrose and polyethylene glycol to ethanol a and stirring evenly, then adding single-walled carbon nanotubes CNT-II with a diameter of 1-3 nm and a length of 15-30 μm, wherein the mass ratio of CNT-II, sucrose, polyethylene glycol and ethanol a is 1:4.5:0.5:94, then adding a certain amount of ethanol b, the mass ratio of ethanol b to ethanol a is 1.28:1, stirring and dispersing at 1000 r / min for 1 h, and then ultrasonically dispersing at a frequency of 60 kHz for 0.5 h to obtain CNT-II dispersion slurry;

[0068] (4) Composite of silicon-based modified material and graphite: The silicon-based modified material and artificial graphite with a particle size of 6 μm were added to the CNT-II dispersion slurry, wherein the mass ratio of nano-silicon, artificial graphite and CNT-II was 30:53:1, and then dispersed at a high speed of 1500 r / min for 2 h to obtain a dispersion slurry with a solid content of 30%, and granulated using a two-fluid spray equipment. The spray drying pressure was 0.45 MPa, and the inlet and outlet temperatures were set to 170° C. and 90° C., respectively, to obtain a silicon-based modified composite material;

[0069] (5) Preparation of CNT-III dispersed powder: Multi-walled carbon nanotubes CNT-III with a diameter of 30-40 nm and a length of 20 μm and coal tar pitch with a softening point of 250°C and a particle size of 100 μm were added into a jet mill, and the mass ratio of multi-walled carbon nanotubes CNT-III to coal tar pitch was 7.89:100. The mixture was crushed at a frequency of 150 Hz to obtain mixed particles of multi-walled carbon nanotubes and asphalt. The mixture was then heated to 265°C and kneaded for 2 h in a kneader. The discharged material was cooled and crushed, and then put into a jet mill and crushed again to obtain CNT-III dispersed powder uniformly dispersed in the asphalt.

[0070] (6) Post-treatment of silicon-based modified composite materials: The silicon-based modified composite materials and CNT-III dispersed powders are added into a high-temperature coating kettle, wherein the mass ratio of CNT-II to CNT-III in the silicon-based modified composite materials is 1:0.6, and stirred at a speed of 400 r / min under the protection of N2 atmosphere, and heated to 320°C for heat treatment for 3 h to fully soften the CNT-III dispersed powder to fill and coat the silicon-based modified composite materials, and then heated to 900°C at 5°C / min under the protection of N2 in a high-temperature box furnace and kept for 2 h to obtain a silicon-based negative electrode material for lithium-ion batteries.

[0071] Example 3

[0072] (1) preparing a CNT-I dispersion slurry: adding a silane coupling agent γ-aminopropylmethyldiethoxysilane to a solution of ethanol and water and stirring evenly, wherein the mass ratio of γ-aminopropylmethyldiethoxysilane to water is 1:4; adding hydroxy carbon nanotubes CNT-I with a diameter of 5-10 nm and a length of 2 μm and asphalt according to a mass ratio of CNT-I, γ-aminopropylmethyldiethoxysilane and asphalt of 0.1:0.02:0.1, wherein the mass fraction of CNT-I in the slurry is 0.5%, ultrasonicating at a frequency of 20 kHz for 1.5 h, and then heating to 100° C. and stirring under reflux for 2 h to obtain a CNT-I dispersion slurry;

[0073] (2) Modification of silicon-based materials: Add nano-silicon with a particle size of 300 nm to the CNT-I dispersion slurry, wherein the mass ratio of nano-silicon to CNT-I is 10:0.5, stir and disperse at 400 r / min for 2 h, separate and dry, and heat to 800°C in an Ar atmosphere at 5°C / min for 2 h to obtain a silicon-based modified material;

[0074] (3) preparing CNT-II dispersion slurry: adding phenolic resin and polyvinyl pyrrolidone to ethanol a and stirring evenly, then adding single-walled carbon nanotubes CNT-II with a diameter of 1-3 nm and a length of 15-30 μm, wherein the mass ratio of CNT-II, phenolic resin, polyvinyl pyrrolidone and ethanol a is 0.1:3:0.05:96.85, then adding a certain amount of ethanol b, the mass ratio of ethanol b to ethanol a is 1.28:1, stirring and dispersing at 400 r / min for 2 h, and then ultrasonically dispersing at a frequency of 40 kHz for 1.5 h to obtain CNT-II dispersion slurry;

[0075] (4) Composite of silicon-based modified material and graphite: The silicon-based modified material and artificial graphite with a particle size of 10 μm were added to the CNT-II dispersion slurry, wherein the mass ratio of nano-silicon, artificial graphite and CNT-II was 10:80:0.1, and the dispersion slurry with a solid content of 30% was obtained at a high-speed dispersion speed of 1500 r / min for 2 h. The granulation was carried out using a two-fluid spray equipment, the spray drying pressure was 0.5 MPa, and the inlet and outlet temperatures were set to 180° C. and 100° C., respectively, to obtain a silicon-based modified composite material;

[0076] (5) Preparation of CNT-III dispersed powder: Multi-walled carbon nanotubes CNT-III with a diameter of 20-30 nm and a length of 30 μm and coal tar pitch with a softening point of 230°C and a particle size of 80 μm were added into a jet mill, and the mass ratio of multi-walled carbon nanotubes CNT-III to coal tar pitch was 6.08:100. The particles were crushed at a frequency of 120 Hz to obtain mixed particles of multi-walled carbon nanotubes and asphalt. The particles were then heated to 245°C and kneaded in a kneader for 5 h. The discharged particles were cooled and crushed, and then put into a jet mill and crushed again to obtain CNT-III dispersed powder uniformly dispersed in the asphalt.

[0077] (6) Post-treatment of silicon-based modified composite materials: The silicon-based modified composite materials and CNT-III dispersed powders are added into a high-temperature coating kettle, wherein the mass ratio of CNT-II to CNT-III in the silicon-based modified composite materials is 1:3.8, and stirred at a speed of 200 r / min under the protection of Ar atmosphere, and heated to 300°C for heat treatment for 5 h to fully soften the CNT-III dispersed powders to fill and coat the silicon-based modified composite materials, and then heated to 800°C at a speed of 10°C / min under the protection of Ar in a high-temperature box furnace and kept for 5 h to obtain a silicon-based negative electrode material for lithium-ion batteries.

[0078] Example 4

[0079] (1) preparing CNT-I dispersion slurry: adding γ-aminopropyltrimethoxysilane, a silane coupling agent, to a solution of ethanol and water and stirring evenly, wherein the mass ratio of γ-aminopropyltrimethoxysilane to water is 1:8; adding hydroxy carbon nanotubes CNT-I with a diameter of 10-15 nm and a length of 3 μm and phenolic resin according to the mass ratio of CNT-I, γ-aminopropyltrimethoxysilane and phenolic resin of 1.5:0.25:1, wherein the mass fraction of CNT-I in the slurry is 1.5%, ultrasonicating at a frequency of 40 kHz for 0.5 h, and then heating to 60° C. and stirring and refluxing for 6 h to obtain CNT-I dispersion slurry;

[0080] (2) Modification of silicon-based materials: Add nano-silicon with a particle size of 150 nm to the CNT-I dispersion slurry, wherein the mass ratio of nano-silicon to CNT-I is 30:1.5, stir and disperse at 600 r / min for 1.5 h, separate and dry, and heat to 700°C at 3°C / min in a N2 atmosphere for 4 h to obtain a silicon-based modified material;

[0081] (3) preparing CNT-II dispersion slurry: adding glucose and polyvinyl alcohol to ethanol a and stirring evenly, then adding single-walled carbon nanotubes CNT-II with a diameter of 1-1.5 nm and a length of 30-40 μm, wherein the mass ratio of CNT-II, glucose, polyvinyl alcohol and ethanol a is 0.6:3.25:0.4:95.75, then adding a certain amount of ethanol b, the mass ratio of ethanol b to ethanol a is 1.17:1, stirring and dispersing at 800 r / min for 1.5 h, and then ultrasonically dispersing at a frequency of 60 kHz for 0.5 h to obtain CNT-II dispersion slurry;

[0082] (4) Composite of silicon-based modified material and graphite: The silicon-based modified material and artificial graphite with a particle size of 8 μm are added to the CNT-II dispersed slurry, wherein the mass ratio of nano-silicon, artificial graphite and CNT-II is 30:52:0.6, and then dispersed at a high speed of 1500 r / min for 2 h to obtain a dispersed slurry with a solid content of 30%, and granulated using a two-fluid spray equipment. The spray drying pressure is 0.3 MPa, and the inlet and outlet temperatures are set to 120° C. and 60° C., respectively, to obtain a silicon-based modified composite material;

[0083] (5) Preparation of CNT-III dispersed powder: Multi-walled carbon nanotubes CNT-III with a diameter of 20-30 nm and a length of 30 μm and petroleum asphalt with a softening point of 280°C and a particle size of 80 μm are added into a jet mill, and the mass ratio of multi-walled carbon nanotubes CNT-III to coal tar is 10:100. The mixture is crushed at a frequency of 140 Hz to obtain mixed particles of multi-walled carbon nanotubes and asphalt. The mixture is then heated to 300°C in a kneader and kneaded for 2 h. The discharged material is cooled and crushed, and then put into a jet mill and crushed again to obtain CNT-III dispersed powder uniformly dispersed in the asphalt.

[0084] (6) Post-treatment of silicon-based modified composite materials: The silicon-based modified composite materials and CNT-III dispersed powders are added into a high-temperature coating kettle, wherein the mass ratio of CNT-II to CNT-III in the silicon-based modified composite materials is 0.6:1, and stirred at a speed of 300 r / min under the protection of N2 atmosphere, and heated to 400°C for heat treatment for 2 h to fully soften the CNT-III dispersed powders to fill and coat the silicon-based modified composite materials, and then heated to 1100°C at 3°C / min under the protection of N2 in a high-temperature box furnace and kept for 0.5 h to obtain silicon-based negative electrode materials for lithium-ion batteries.

[0085] Example 5

[0086] Preparation of CNT-I dispersion slurry: adding γ-aminopropylmethyldiethoxysilane, a silane coupling agent, to a solution prepared by ethanol and water and stirring evenly, wherein the mass ratio of γ-aminopropylmethyldiethoxysilane to water is 1:4; adding hydroxy carbon nanotubes CNT-I with a diameter of 5-15 nm and a length of 0.5 μm and phenolic resin according to the mass ratio of CNT-I, γ-aminopropylmethyldiethoxysilane and phenolic resin of 0.1:0.02:0.2, wherein the mass fraction of CNT-I in the slurry is 0.1%, ultrasonicating at a frequency of 20 kHz for 1.5 h, and then heating to 100° C. and stirring and refluxing for 2 h to obtain CNT-I dispersion slurry;

[0087] (1) Modification of silicon-based materials: Add nano-silicon with a particle size of 250 nm to the CNT-I dispersion slurry, wherein the mass ratio of nano-silicon to CNT-I is 10:0.1, stir and disperse at 800 r / min for 1 h, separate and dry, and heat to 700°C at 3°C / min in a N2 atmosphere for 4 h to obtain a silicon-based modified material;

[0088] (2) preparing CNT-II dispersion slurry: adding citric acid and polyvinyl alcohol to ethanol a and stirring evenly, then adding single-walled carbon nanotubes CNT-II with a diameter of 1-3 nm and a length of 15-30 μm, wherein the mass ratio of CNT-II, citric acid, polyvinyl alcohol and ethanol a is 0.2:8.37:0.1:91.33, then adding a certain amount of ethanol b, the mass ratio of ethanol b to ethanol a is 1.53:1, stirring and dispersing at 800 r / min for 1.5 h, and then ultrasonically dispersing at a frequency of 40 kHz for 1.5 h to obtain CNT-II dispersion slurry;

[0089] (3) Composite of silicon-based modified material and graphite: The silicon-based modified material and artificial graphite with a particle size of 8 μm were added to the CNT-II dispersed slurry, wherein the mass ratio of nano-silicon, artificial graphite and CNT-II was 10:80:0.2, and then dispersed at a high speed of 1500 r / min for 2 h to obtain a dispersed slurry with a solid content of 30%, and granulated using a two-fluid spray equipment. The spray drying pressure was 0.4 MPa, and the inlet and outlet temperatures were set to 140° C. and 70° C., respectively, to obtain a silicon-based modified composite material;

[0090] (4) Preparation of CNT-III dispersed powder: Multi-walled carbon nanotubes CNT-III with a diameter of 20-40 nm and a length of 10 μm and petroleum asphalt with a softening point of 280°C and a particle size of 80 μm are added to a jet mill, and the mass ratio of multi-walled carbon nanotubes CNT-III to coal tar is 1:100. The mixture is crushed at a frequency of 100 Hz to obtain mixed particles of multi-walled carbon nanotubes and asphalt. The mixture is then heated to 300°C in a kneader and kneaded for 2 h. The discharged material is cooled and crushed, and then put into a jet mill and crushed again to obtain CNT-III dispersed powder uniformly dispersed in the asphalt.

[0091] (5) Post-treatment of silicon-based modified composite materials: The silicon-based modified composite materials and CNT-III dispersed powders are added into a high-temperature coating kettle, wherein the mass ratio of CNT-II to CNT-III in the silicon-based modified composite materials is 2:0.1, stirred at a speed of 300 r / min under the protection of N2 atmosphere, heated to 400°C for 1 h to fully soften the CNT-III dispersed powders to fill and coat the silicon-based modified composite materials, and then heated to 1000°C at 3°C / min under the protection of N2 in a high-temperature box furnace for 2 h to obtain silicon-based negative electrode materials for lithium-ion batteries.

[0092] Example 6

[0093] (1) preparing a CNT-I dispersion slurry: adding γ-aminopropyltrimethoxysilane, a silane coupling agent, to a solution of ethanol and water and stirring the mixture evenly, wherein the mass ratio of γ-aminopropyltrimethoxysilane to water is 1:8; adding hydroxy carbon nanotubes CNT-I with a diameter of 5-10 nm and a length of 2 μm and asphalt in a mass ratio of CNT-I, γ-aminopropyltrimethoxysilane and asphalt of 1:0.25:0.8, wherein the mass fraction of CNT-I in the slurry is 1%, ultrasonically treating the mixture at a frequency of 40 kHz for 0.5 h, and then heating the mixture to 60° C. and stirring and refluxing for 6 h to obtain a CNT-I dispersion slurry;

[0094] (2) Modification of silicon-based materials: Add nano-silicon with a particle size of 250 nm to the CNT-I dispersion slurry, wherein the mass ratio of nano-silicon to CNT-I is 30:1, stir and disperse at 600 r / min for 1.5 h, separate and dry, and heat to 800 °C at 5 °C / min in a N2 atmosphere for 2 h to obtain a silicon-based modified material;

[0095] (3) preparing CNT-II dispersion slurry: adding phenolic resin and polyvinyl pyrrolidone to ethanol a and stirring evenly, then adding single-walled carbon nanotubes CNT-II with a diameter of 1-3 nm and a length of 15-30 μm, wherein the mass ratio of CNT-II, phenolic resin, polyvinyl pyrrolidone and ethanol a is 0.8:10:0.5:88.7, then adding a certain amount of ethanol b, the mass ratio of ethanol b to ethanol a is 1.46:1, stirring and dispersing at 1000 r / min for 1 h, and then ultrasonically dispersing at a frequency of 50 kHz for 1 h to obtain CNT-II dispersion slurry;

[0096] (4) Composite of silicon-based modified material and graphite: The silicon-based modified material and artificial graphite with a particle size of 8 μm are added to the CNT-II dispersed slurry, wherein the mass ratio of nano-silicon, artificial graphite and CNT-II is 30:50:0.8, and then dispersed at a high speed of 1500 r / min for 2 h to obtain a dispersed slurry with a solid content of 30%, and granulated using a two-fluid spray equipment. The spray drying pressure is 0.5 MPa, and the inlet and outlet temperatures are set to 180° C. and 100° C., respectively, to obtain a silicon-based modified composite material;

[0097] (5) Preparation of CNT-III dispersed powder: Multi-walled carbon nanotubes CNT-III with a diameter of 30-40 nm and a length of 20 μm and coal tar pitch with a softening point of 250°C and a particle size of 100 μm were added into a jet mill, and the mass ratio of multi-walled carbon nanotubes CNT-III to coal tar pitch was 2.83:100. The mixed particles of multi-walled carbon nanotubes and asphalt were obtained by pulverizing at a frequency of 180 Hz. The mixed particles were then heated to 265°C and kneaded in a kneader for 3 h. The discharged material was cooled and crushed, and then put into a jet mill and pulverized again to obtain CNT-III dispersed powder uniformly dispersed in the asphalt.

[0098] (6) Post-treatment of silicon-based modified composite materials: The silicon-based modified composite materials and CNT-III dispersed powders are added into a high-temperature coating kettle, wherein the mass ratio of CNT-II to CNT-III in the silicon-based modified composite materials is 8:1.5, and stirred at a speed of 300 r / min under the protection of N2 atmosphere, and heated to 365°C for heat treatment for 1 h to fully soften the CNT-III dispersed powder to fill and coat the silicon-based modified composite materials, and then heated to 1000°C at 3°C / min under the protection of N2 in a high-temperature box furnace and kept for 2 h to obtain a silicon-based negative electrode material for lithium-ion batteries.

[0099] Comparative Example 1

[0100] The difference is that in step (1), the mass ratio of CNT-I, γ-aminopropyltriethoxysilane and polyvinylpyrrolidone is 0:0.2:1.5, and the rest is referred to Example 1.

[0101] Comparative Example 2

[0102] The difference is that in step (3), the mass ratio of CNT-II, citric acid, Triton X-100 and ethanol a is 0:8.8:0.2:91, and the rest is referred to Example 1.

[0103] Comparative Example 3

[0104] The difference is that CNT-III is not added in step (5), and in step (6), the mass ratio of CNT-II to coal tar pitch in the silicon-based modified composite material is 0.5:3.3, and the rest is referred to Example 1.

[0105] Comparative Example 4

[0106] The difference is that step (5) is cancelled, CNT-III dispersed powder is not used in step (6), and in step (3), the mass ratio of CNT-II, citric acid, Triton X-100 and ethanol a is 0.5:11.6:0.2:87.7, and the rest is the same as Example 1.

[0107] Comparative Example 5

[0108] The difference is that in step (1), the mass ratio of CNT-I, γ-aminopropyltriethoxysilane and polyvinylpyrrolidone is 0:0.2:1.5, in step (3), the mass ratio of CNT-II, citric acid, Triton X-100 and ethanol a is 0:8.8:0.2:91, in step (5), CNT-III is not added, in step (6), the mass ratio of CNT-II and coal tar in the silicon-based modified composite material is 0:3.3, and the rest is referred to Example 1.

[0109] The silicon-based negative electrode materials for lithium-ion batteries prepared in Examples 1-6 and Comparative Examples 1-5 were tested using the following method:

[0110] The morphology of the silicon-based negative electrode material for lithium-ion batteries prepared by the present invention was observed using a scanning electron microscope S4800-I of Hitachi.

[0111] The following method was used to test the electrochemical cycle performance: the negative electrode active material: sodium carboxymethyl cellulose (CMC): conductive carbon black (SP): styrene-butadiene rubber (SBR) was mixed in a mass ratio of 94.5:1.5:1.5:2.5 to prepare the working electrode, which was coated on the copper foil current collector and vacuum dried to obtain the negative electrode plate; then the lithium plate, 1 mol / L LiPF6 three-component mixed solvent were mixed with electrolyte in the ratio of EC:DMC:EMC=1:1:1 (v / v), Celgard2400 diaphragm, and shell to assemble the button battery using conventional production process. The charge and discharge test of the button battery was carried out on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd., and the charge and discharge voltage was limited to 0.05-1.5V. The cycle performance test was carried out at room temperature, 0.1C constant current charge and discharge, and the rate performance test conditions were under the conditions of 0.1C and 3C respectively, 3C / 0.1C=3C current discharge specific capacity / 0.1C current discharge specific capacity.

[0112] The test results are shown in Table 1.

[0113] Table 1 Relevant performance data of Examples 1-6 and Comparative Examples 1-5

[0114]

[0115] As can be seen from Table 1, the silicon-based negative electrode materials prepared by adding carbon nanotubes of different sizes and dispersion modes in three stages of silicon-based material modification, silicon-based modified material and graphite composite and composite material post-treatment process in Example 1-Example 5 can effectively improve the dispersibility of silicon-based materials and carbon nanotubes in the entire composite material, while increasing the mechanical strength of the silicon-based negative electrode material itself and the bonding ability between different components and the overall conductivity, so that it has excellent cycle performance and rate charge and discharge performance. At the same time, the expansion rate of the pole piece is significantly improved for 500 times, which shows that the silicon-based material for lithium-ion batteries provided by the present invention can effectively inhibit the expansion of the pole piece and the peeling of the active material during the electrochemical cycle, thereby significantly improving the cycle performance of the lithium-ion battery.

[0116] By comparing Example 1 with Comparative Example 1, it can be seen that Comparative Example 1 does not use CNT-I to coat nano-silicon, and cannot restrain the expansion of silicon, so the material has a large expansion rate and poor cycle. Example 1 uses short straight multi-walled carbon nanotubes with better rigidity, which can more easily penetrate the pyrolytic carbon layer and maintain good electrical contact with the surrounding conductive materials, thereby enhancing the cycle stability and rate performance of silicon-based materials.

[0117] By comparing Example 1 and Comparative Example 2, it can be seen that since Comparative Example 2 does not add CNT-II with high flexibility and conductivity, the binder and dispersant cannot restrain the expansion of nano-silicon after high-temperature carbonization, and the rate performance and cycle stability of the entire material are significantly reduced.

[0118] By comparing Example 1 and Comparative Example 3, it can be seen that the CNT-III filled into the microspheres will establish a connection with the conductive network formed by CNT-I and CNT-II to form a more stable three-dimensional network structure. At the same time, the carbon source pyrolytic carbon makes the internal structure of the entire composite material dense and the surface uniform, which plays a role in buffering the expansion of the internal material, avoiding the contact of the silicon-based material with the electrolyte, and improving the stability of the material.

[0119] By comparing Example 1 and Comparative Example 4, it can be seen that Comparative Example 4 has no surface-coated carbon layer, there are a large number of pores inside the material, the tap density is low, the material particle strength is poor, and the structure is unstable. During the cycle process, silicon is in direct contact with the electrolyte, resulting in reduced capacity and first efficiency, and the cycle performance also deteriorates.

[0120] By comparing Example 1 and Comparative Example 5, it can be seen that the cycle performance, rate performance and first efficiency of Comparative Example 5, which does not add any form of carbon nanotubes, are significantly reduced. This is because carbon nanotubes of different diameters and lengths are cross-linked with each other to form a high-strength conductive network, which can serve as a buffer skeleton and build a fast electron transmission channel between the silicon-based material and the surrounding conductive material, which is more conducive to solving the problems of poor conductivity and volume expansion of the composite material.

[0121] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing a silicon-based negative electrode material, comprising the following steps: (1) Silicon-based material modification: the silicon-based material and CNT-Ⅰ dispersion slurry are mixed, separated, dried, and sintered under an inert atmosphere to obtain a silicon-based modified material; (2) Composite of silicon-based modified material and graphite: The silicon-based modified material, graphite and CNT-II dispersed slurry are mixed and spray-dried to obtain a silicon-based modified composite material; (3) Post-treatment of silicon-based modified composite materials: using CNT-III dispersed powder uniformly dispersed in the coating agent to fill and coat the silicon-based modified composite materials, and carbonizing at high temperature; The preparation method of the CNT-Ⅰ dispersed slurry comprises the following steps: adding a silane coupling agent to an ethanol aqueous solution, mixing uniformly, adding hydroxyl carbon nanotubes CNT-Ⅰ and an organic carbon source to disperse uniformly, and then heating, stirring, and refluxing to obtain a CNT-Ⅰ dispersed slurry; The preparation method of the CNT-II dispersed slurry comprises the following steps: uniformly mixing a binder, a dispersant and a solvent a, adding single-walled carbon nanotubes CNT-II and a solvent b thereto, and dispersing to obtain a CNT-II dispersed slurry; The method for preparing the CNT-III dispersed powder uniformly dispersed in the coating agent comprises the following steps: grinding the multi-walled carbon nanotubes CNT-III and the coating agent powder in a jet mill to obtain a mixed powder of the multi-walled carbon nanotubes and the coating agent, kneading the mixed powder in a kneader, cooling the discharged material and crushing it, and then grinding it in a jet mill; The diameter of the hydroxyl carbon nanotube CNT-I is 5nm-15nm, and the length is 0.5μm-2μm; the diameter of the single-walled carbon nanotube CNT-II is 1nm-3nm, and the length is 15μm-40μm, and the aspect ratio is greater than 10000; the diameter of the multi-walled carbon nanotube CNT-III is 20-40nm, and the length is 10-30μm.

2. The preparation method according to claim 1, characterized in that: The step (3) comprises the following steps: filling and coating the silicon-based modified composite material with CNT-III dispersed powder uniformly dispersed in the coating agent, heat-treating the silicon-based modified composite material in a heating mixing device under the protection of an inert atmosphere, and then high-temperature carbonizing the silicon-based modified composite material under the inert atmosphere.

3. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of silicon-based material to CNT-Ⅰ is (10-30): (0.1-1.5).

4. The preparation method according to claim 1, characterized in that: In the preparation method of the CNT-Ⅱ dispersed slurry, based on the total mass of CNT-Ⅱ, binder, dispersant and solvent a as 100%, CNT-Ⅱ accounts for 0.1-1%, binder accounts for 3-10%, dispersant accounts for 0.05-0.5%, and solvent a accounts for 88.7-96.85%.

5. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the graphite, CNT-II and the silicon-based material in the step (1) is (50-80); (0.1-1): (10-30).

6. The preparation method according to claim 1, characterized in that: In the step (3), the mass ratio of CNT-II to CNT-III contained in the silicon-based modified composite material is (0.1-1): (0.01-1).

7. The preparation method according to claim 1, characterized in that: In the method for preparing CNT-III dispersed powder uniformly dispersed in a coating agent, the coating agent includes one or more of a thermoplastic resin and asphalt.

8. The preparation method according to claim 7, characterized in that: The asphalt includes one or more of petroleum asphalt and coal-based asphalt.

9. The preparation method according to claim 7, characterized in that: The softening point of the asphalt is 200-300° C., and the particle size D50 is 50-100 μm.

10. The preparation method according to claim 7, characterized in that: The softening point of the asphalt is 230-280°C.

Citation Information

Patent Citations

  • A silicon-carbon nanotube sphere and its preparation method, a battery anode and a lithium-ion battery

    CN106169564B

  • A high-capacity silicon-carbon anode active material, its preparation method, and its application

    CN109301215B

  • High-energy-density and high-power-density negative electrode material for lithium ion battery and preparation method

    CN109755522A

  • Silicon / graphite composite material, preparation method thereof and application thereof

    CN110600704A